2008
DOI: 10.1021/bi800140q
|View full text |Cite
|
Sign up to set email alerts
|

Spider Minor Ampullate Silk Proteins Are Constituents of Prey Wrapping Silk in the Cob WeaverLatrodectus hesperus

Abstract: Spiders spin high performance fibers with diverse biological functions and mechanical properties. Molecular and biochemical studies of spider prey wrapping silks have revealed the presence of the aciniform silk fibroin AcSp1-like. In our studies we demonstrate the presence of a second distinct polypeptide present within prey wrapping silk. Combining matrix-assisted laser desorption ionization tandem time-of-flight mass spectrometry and reverse genetics, we have isolated a novel gene called MiSp1-like and demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 26 publications
(49 reference statements)
1
37
0
Order By: Relevance
“…The silk used to wrap preys caught in the web is produced by the aciniform (Ac) glands, although it has been shown that, in addition to Ac fibers, Ma and Mi silk fibers are also found in the wrapping net spun around a prey. 56 Interestingly, Raman spectromicroscopy has clearly confirmed the above finding, showing that this technique is also an efficient and simple tool to identify the nature of silk fibers in harvested biological samples. 57 Until recently, no data was available regarding the structural organization of the Ac silk, but its amino acid sequence has been determined for Argiope trifasciata.…”
Section: The Molecular Structure Of Other Silk Fibersmentioning
confidence: 60%
“…The silk used to wrap preys caught in the web is produced by the aciniform (Ac) glands, although it has been shown that, in addition to Ac fibers, Ma and Mi silk fibers are also found in the wrapping net spun around a prey. 56 Interestingly, Raman spectromicroscopy has clearly confirmed the above finding, showing that this technique is also an efficient and simple tool to identify the nature of silk fibers in harvested biological samples. 57 Until recently, no data was available regarding the structural organization of the Ac silk, but its amino acid sequence has been determined for Argiope trifasciata.…”
Section: The Molecular Structure Of Other Silk Fibersmentioning
confidence: 60%
“…A, major ampullate; B, minor ampullate; C, flagelliform; D, aggregate; E, aciniform; F, tubuliform; and G, pyriform. Data from the major and minor ampullate glands, as well as the aciniform gland were previously determined (6,12). Fig.…”
Section: Amino Acid Composition Analyses Of the Luminal Contents Of Tmentioning
confidence: 99%
“…Over the past 20 years, seven distinct members of the silk gene family have been identified and characterized at the molecular level, which include the silk proteins MaSp1 and MaSp2 (dragline silk) (3)(4)(5), AcSp1 or AcSp1-like (wrapping silk and egg case silk) (6,7), TuSp1 (egg case silk)(8 -11), MiSp1 and MiSp2 or MiSp1-like (temporary spiral capture silk or web reinforcement silk) (12,13), and Flag silk (capture spiral silk in orb weavers) (14). These spider fibroins have revealed that they share a number of distinctive properties, including four fundamental amino acid repeat motifs that characterize the majority of the family: (i) alternating glycine alanine couplets (GA n ), (ii) polyalanine blocks (A n ), (iii) GGX (X ϭ subset of residues, which include Leu, Ile, and Ala), and (iv) GPGX n .…”
mentioning
confidence: 99%
“…34 It has also been found in the wrapping net spun around prey. 35 Cocoon silk is produced by the tubuliform gland of female spiders during the reproductive season 36 and is used to make the cocoon outer egg sac. As shown in Table 1, MiS has a lower stress at rupture than MaS, but its extensibility is higher.…”
Section: Introductionmentioning
confidence: 99%